COMPREHENDING AND CONSUMER ENGAGEMENT IN VIRTUAL BRANDCOMMUNITIES - Makki, Ali (E-Journal VFU, 2025)
Congruity theory is used in this study to examine the dynamics of customerparticipation in online brand communities (OBCs). It specifically looks at how important aspects that drive customer engagement are self-brand image congruity and value congruity. As a natural byproduct of customer interaction, brand loyalty is also closely examined. The paper provides aconceptual model that shows the connections between various components that are theoretically proposed.
Keywords: Brand Engagement; Value Congruity; Self-Brand Image Congruity; Congruity Theory; Online Brand Communities (OBCs); Online Surveys; Gender Moderation; Consumer Behavior; Social Media; Brand Loyalty, Digital Marketing